Legal Policy for Regional Innovation in the Transformation of Adaptive Government Bureaucracy - Evendia, Malicia; Tisnanta, HS; Ridlwan, Zulkarnain; Firmansyah, Ade Arif (Journal of Ecohumanism, 2025)
The way in which local government is organized affects the results in achieving the goals of decentralization. For this reason, regional innovation as a driving force in development cannot be separated from the influence of local government bureaucracy. Decentralization, which stems from democratic values, places public participation as a priority that must be upheld in every policy issued by the government. This paper will elaborate on how the determination of innovation legal policy and adaptive local government bureaucracy in the perspective of regional autonomy, as well as its relationship with community participation as a basis in the substance of regional innovation legal policy. Using a conceptual approach and a legal approach, the results of this study show that regional innovation legal policies that accommodate guarantees of community participation are an important element in producing bottom-up innovations in accordance with the challenges and potential of the region in development efforts. Adaptive local government bureaucracy is an important aspect in the success cycle of regional innovation instruments in improving community welfare in the perspective of autonomy.